Static load identification of nonlinear structure based on internal force estimation exemplified by underground straight-wall arch structure. (May 2023) - Zheng, Kaikai; Yuan, Jian; Yang, Kangkang; Qu, Yiwen; Gao, Chengqiang; Shi, Jun
Abstract: Due to the complexity of the interaction between surrounding rock and support structure, underground structures have complex and time-varying boundary conditions that is difficult to determine in advance. It is necessary to perform damage/load identification of underground structures in real time, but there is a lack of relevant studies. Therefore, a load inversion method of nonlinear structure based on internal force estimation is proposed in this paper. First, a static damage experiment of straight-wall arch model was conducted to analyze its crack development pattern and damage mode. Then, interpolation and integration method (IIM) was used to calculate the internal force of the section through numerous strain data, and its estimation accuracy was verified by experiment and simulation. Finally, a new method of load identification, IVW-LAD (Incremental Variable Weighted - Least Absolute Deviation), using internal forces as optimization variables was proposed and validated. In summary, the findings of this paper can provide a reference for health diagnosis and load identification of nonlinear underground structures.